Young adults’ perspectives on living with kidney failure: a systematic review and thematic synthesis of qualitative studies - Pippa Bailey; Alexander Hamilton; Rhian Clissold; Carol Inward; Fergus Caskey; Yoav Ben‐Shlomo; Amanda Owen‐Smith (2018)
Introduction Young adults fare worse than younger adolescents or older adults on a broad range of health indicators. Those with a chronic illness such as renal failure are a particularly vulnerable group, who experience poor outcomes compared with both children and older adults. Understanding how being in receipt of renal replacement therapy (RRT) affects the lives of young adults might help us to better prepare and support these individuals for and on RRT, and improve outcomes. This study aimed to synthesise research describing young adults’ experiences of the psychosocial impact of kidney failure and RRT. Design A systematic literature review identified qualitative research reporting the perspectives of people aged 16–30 years receiving RRT on the psychosocial impact of renal failure. Electronic databases (including Medline/EMBASE/PsycINFO/ASSIA) were searched to November 2017 for full-text papers. The transparency of reporting of each study was assessed using the Consolidated Criteria for Reporting Qualitative Health Research (COREQ) framework. Quality was assessed using the Critical Appraisal Skills Programme qualitative checklist. An inductive thematic synthesis was undertaken. Participants Seven studies from five different countries were included, comprising 123 young adults receiving RRT. Results Comprehensiveness of reporting was variable: studies reported 9–22 of the 32 COREQ-checklist items. Three global themes about the impact of kidney failure on young adults were identified: (1) difference desiring normality, (2) thwarted or moderated dreams and ambitions, and (3) uncertainty and liminality. These reflected five organising themes: (1) physical appearance and body image, (2) activity and participation, (3) educational disruption and underachievement, (4) career ambitions and employment difficulties, and (5) social isolation and intimate relationships. Conclusions Across different countries and different healthcare settings, young adults on RRT experience difference and liminality, even after transplantation. Tailored social and psychological support is required to allow young adults to experience wellness while in receipt of RRT, and not have life on hold.